Editorial: Multi-omics studies on aging and age-related diseases - Wang, He-Ping; Basisty, Nathan; Qu, Jia-Hua; Wang, Xiaoman (Frontiers in cell and developmental biology, 2024)
Through LASSO regression method and Cox regression analysis, three genes GPC3, GPX3 and PRICKLE1 were identified as prognostic risk signatures for overall survival among gastric cancer patients, offering tailored diagnostic and treatment strategies for gastric cancer. In addition to cancers and AD that the four articles in this Research Topic focused on, other aging processes and age-related pathologies, such as metabolic syndrome, cardiovascular diseases, frailty and others, also benefit from the development and application of multi-omic techniques (Zheng et al., 2022; Sahu et al., 2023; Zhang et al., 2023). Conflict of interest The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.